Fetal loss after chorionic villus sampling in twin pregnancy. (1st July 2021) - Elger, T.; Akolekar, R.; Syngelaki, A.; De Paco Matallana, C.; Molina, F. S.; Gallardo Arozena, M.; Chaveeva, P.; Persico, N.; Accurti, V.; Kagan, K. O.; Prodan, N.; Cruz, J.; et al.
ABSTRACT: Objective: To estimate the chorionic villus sampling (CVS)‐related risk of fetal loss in twin pregnancy after adjustment for chorionicity, nuchal translucency thickness (NT), intertwin discordance in crown–rump length (CRL), maternal demographic characteristics and serum pregnancy‐associated plasma protein‐A (PAPP‐A) and free β‐human chorionic gonadotropin (β‐hCG). Methods: This was a multicenter study from eight fetal medicine units in which the leadership were trained at the Harris Birthright Research Centre for Fetal Medicine in London, UK, and in which the protocols for screening, invasive testing and pregnancy management are similar. Data were obtained prospectively from women with twin pregnancy undergoing routine ultrasound examination at 11–13 weeks' gestation. Multivariable logistic regression analysis with backward stepwise elimination was used to examine whether CVS provided a significant independent contribution to the prediction of risk of fetal loss after adjusting for maternal and pregnancy characteristics, including maternal age, racial origin and weight, method of conception, smoking status, parity, chorionicity, intertwin discordance in CRL, fetal NT ≥ 95 th percentile and free β‐hCG and PAPP‐A multiples of the median. Similarly, within the CVS group, multivariable logistic regression analysis was used to investigate the effect of the number of intrauterine needle insertions and size of the needle on the risk of fetal loss. Results: The study population of 8581 twin pregnancies undergoing ultrasound examination at 11–13 weeks' gestation included 316 dichorionic and 129 monochorionic twins that had CVS. First, in twin pregnancies undergoing CVS, compared to those not undergoing CVS, there was a 2‐fold increased risk of fetal loss at < 24 weeks' gestation and of loss at any stage in pregnancy. Second, the factors providing a significant independent contribution to the prediction of miscarriage or fetal loss in twin pregnancy were increased maternal weight, black racial origin, monochorionicity, and more so monoamnionicity, large intertwin discordance in CRL and increased fetal NT, and, in the case of fetal loss at any stage, there was also a contribution from assisted conception and low serum PAPP‐A. Third, after adjustment for maternal and pregnancy characteristics, CVS did not provide a significant contribution to the risk of fetal loss. Fourth, in twin pregnancies that had CVS, there was no significant contribution to fetal loss from the number of intrauterine needle insertions or needle size. Conclusion: The 2‐fold increased risk of fetal loss following CVS in twin pregnancy can, to a great extent, be explained by maternal and pregnancy characteristics rather than the invasive procedure itself. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : A video abstract of this article is available online here . This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Muerte fetal tras la biopsia de vellosidades coriónicas en el embarazo de gemelos Objetivo: Estimar el riesgo de muerte fetal relacionado con la biopsia de vellosidades coriónicas (BVC) en el embarazo de gemelos una vez hechos los ajustes para tener en cuenta la corionicidad, el grosor de la translucidez nucal (TN), la discordancia entre gemelos en la longitud céfalo‐caudal (LCC), las características demográficas maternas, la proteína plasmática A asociada al embarazo (PAPP‐A, por sus siglas en inglés) y la hormona gonadotrópica coriónica humana (subunidad B) libre (β‐hCG). Métodos: Este fue un estudio multicéntrico de ocho unidades de medicina fetal en las que la gerencia se formó en el Harris Birthright Research Centre for Fetal Medicine de Londres (Reino Unido), en las cuales los protocolos de cribado, pruebas agresivas y la atención médica al embarazo son similares. Los datos se obtuvieron de forma prospectiva de mujeres embarazadas con gemelos que se sometieron a una ecografía rutinaria a las 11‐13 semanas de gestación. Se utilizó un análisis de regresión logística multivariable con eliminación por etapas hacia atrás para examinar si la BVC contribuía de forma independiente y significativa a la predicción del riesgo de muerte fetal tras los ajustes respecto a las características maternas y del embarazo, como la edad, el origen étnico y el peso de la madre, el método de concepción, el estado de tabaquismo, la paridad, la corionicidad, la discordancia entre gemelos en la LCC, la TN fetal ≥95º percentil y varios múltiplos de la mediana de la β‐hCG libre y la PAPP‐A libre. Del mismo modo, dentro del grupo de BVC, se utilizó un análisis de regresión logística multivariable para investigar el efecto del número de inserciones de agujas intrauterinas y el tamaño de la aguja sobre el riesgo de muerte fetal. Resultados: La población de estudio fue de 8581 embarazos de gemelos que se sometieron a una ecografía a las 11–13 semanas de gestación e incluyó 316 (78, 2%) embarazos bicoriales (BC) y 129 (21, 8%) monocoriales (MC). En primer lugar, en los embarazos de gemelos sometidos a una BVC, en comparación con los que no se sometieron a ella, hubo un riesgo 2 veces mayor de muerte fetal antes de las 24 semanas de gestación y de pérdida en cualquier fase del embarazo. En segundo lugar, los factores que aportaron una contribución independiente significativa a la predicción del aborto o la muerte fetal en el embarazo de gemelos fueron un mayor peso materno, el origen étnico de raza negra, la monocorionicidad, y sobre todo la monoamnionicidad, una gran discordancia entre gemelos en la LCC y una mayor TN fetal, y, en el caso de la muerte fetal en cualquier fase, también contribuyeron la concepción asistida y la PAPP‐A sérica baja. En tercer lugar, tras el ajuste respecto a las características maternas y del embarazo, la BVC no aportó una contribución significativa al riesgo de muerte fetal. En cuarto lugar, en los embarazos de gemelos sometidos a BVC, el número de inserciones de agujas intrauterinas o el tamaño de las mismas no contribuyeron de forma significativa a la muerte fetal. Conclusión: El riesgo dos veces mayor de muerte fetal después de una BVC en el embarazo de gemelos puede, en gran medida, explicarse por las características maternas y del embarazo más que por el procedimiento traumático en sí. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. 摘要: 双胎妊娠中绒膜绒毛取样后的妊娠丢失 目的: 对绒毛膜、胎儿颈项透明膜厚度(NT)、双胎顶臀长(CRL)不一致、母亲的人口学特征和血清妊娠相关的血浆蛋白‐A(PAPP‐A)以及游离β‐人绒毛膜促腺性激素(β‐hCG)的调整后，评估双胎妊娠中与绒膜绒毛取样(CVS)相关的妊娠丢失的风险。 方法: 这是一项由八个胎儿医学单位参与的多中心研究，在英国伦敦的 Harris Birthright研究中心举办了领导力培训，其中对筛检、 侵入性测试和妊娠管理的协议均相似。从双胎妊娠的妇女处预期获得的数据，这些孕妇在妊娠11‐13周进行了常规超声检查。用多变量回归分析 (采用倒退阶梯式去除)来检查在调整了母亲及妊娠特征(包括母亲的年龄、种族和体重、怀孕方法、吸烟状态、胎次、绒毛膜、双胎CRL不一致、胎儿NT大于第95个百分点、游离β‐hCG和PAPP‐A中位倍数)之后，CVS对妊娠丢失风险的预测是否起到一个重大的独立作用。同样地，在CVS组内采用多变量回归分析研究子宫内进针针数和针的大小对妊娠丢失风险的影响。 结果: 研究人群为8581个双胎妊娠(包括进行了CVS的316个双绒毛膜和129个单绒毛膜双胎)，在妊娠11‐13周进行了常规超声检查。首先，进行了CVS的双胎妊娠与未进行过CVS的双胎妊娠对比，在妊娠24周以后妊娠丢失的风险和在妊娠期间任何阶段流产的风险增加了两倍。第二，在双胎妊娠中对流产或妊娠丢失的预测起到重大独立影响的因素有:增加的产妇体重、黑人种族、单绒毛膜(更为明显)、较大的双胎CRL不一致以及增加的胎儿NT，而在任何阶段的妊娠丢失情况中，辅助怀孕和低血清PAPP‐A也起到一定的作用。第三，在对母亲和妊娠特征调整后，CVS并未对妊娠丢失的风险起到重大影响。第四，在进行了CVS的双胎妊娠中，从子宫内进针针数和针的大小来看，并没有对妊娠丢失起到任何重大影响。 结论: 双胎妊娠中在进行了CVS后妊娠丢失风险增加两倍在很大程度上可以用母亲和妊娠特征来解释，而不是侵入性治疗本身。© 2021年国际妇产科超声学会。